HUBUNGAN ANTARA PERILAKU 3M PLUS DENGAN KEJADIAN DBD DI WILAYAH KERJA PUSKESMAS SEMEMI TAHUN 2021 - Dwi Erlina Fristianti; Fitri Rokhmalia; Hadi Suryono (GEMA LINGKUNGAN KESEHATAN, 2022)
One of the serious public health problems is dengue fever which is influenced by environmental factors. One that can affect the increase in the larva free rate with a percentage of 85%. This is due to a lack of public awareness in 3M plus activities on a regular basis. The purpose of this study was to study the relationship between 3M plus behavior and the incidence of dengue fever in the working area of the Sememi Health Center.This type of research is an analytic study which was carried out by case control. The object of the study was 12 samples of DHF patients. Community behavior data obtained from this study is the level of knowledge, attitudes, and actions. Analysis of the data in this study presented a chi-square test to analyze the relationship between 3M plus behavior and the incidence of DHF.Based on observations made on 24 respondents' houses, the respondents' knowledge level met the criteria of sufficient 42%, the attitude of the respondents met the criteria of less than 42%, and the actions of the respondents met the criteria of less than 46%. The results of the Chi square analysis test that there is a relationship between the incidence of DHF and the behavior of respondents with p value 0.05It is necessary to conduct counseling regarding 3M plus efforts, as well as hold community service activities to carry out 3M plus activities directed at cleaning homes and the surrounding environment so that the spread of dengue disease can be reduced.